The epithelial zinc transporter ZIP10 epigenetically regulates human epidermal homeostasis by modulating histone acetyltransferase activity. (5th December 2018) - Bin, B.‐H.; Lee, S.‐H.; Bhin, J.; Irié, T.; Kim, S.; Seo, J.; Mishima, K.; Lee, T.R.; Hwang, D.; Fukada, T.; Cho, E.‐G.
Summary: Background: The skin is the first organ that manifests changes in response to zinc deficiency. However, the molecular mechanism underlying how zinc is involved in skin homeostasis, especially its epigenetic regulation, is largely unknown. Objectives: In this study we demonstrate the importance of zinc levels and the zinc transporter ZIP10 in the epigenetic maintenance of human epidermal homeostasis. Methods: Adult human skin, including skin appendages, were stained with anti‐ZIP10 antibody. Histone acetyltransferase (HAT) activity was assessed after treating human keratinocytes with ZIP10 small interfering (si)RNAs or the zinc chelator TPEN. ZIP10‐ or HAT‐regulated genes were analysed based on limma bioinformatics analysis for keratinocytes treated with ZIP10 siRNAs or a HAT inhibitor, or using a public database for transcription factors. A reconstituted human skin model was used to validate the role of ZIP10 in epidermal differentiation and the functional association between ZIP10 and HAT. Results: ZIP10 is predominantly expressed in the interfollicular epidermis, epidermal appendages and hair follicles. ZIP10 depletion resulted in epidermal malformations in a reconstituted human skin model via downregulation of the activity of the epigenetic enzyme HAT. This decreased HAT activity, resulting from either ZIP10 depletion or treatment with the zinc chelator TPEN, was readily restored by zinc supplementation. Through bioinformatics analysis for gene sets regulated by knockdown of SLC39A10 (encoding ZIP10) and HAT inhibition, we demonstrated that ZIP10 and HATs were closely linked with the regulation of genes related to epidermal homeostasis, particularly filaggrin and metallothionein. Conclusions: Our study suggests that ZIP10‐mediated zinc distribution is crucial for epidermal homeostasis via HATs. Therefore, zinc‐dependent epigenetic regulation could provide alternatives to maintaining healthy skin or alleviating disorders with skin barrier defects. Abstract : What's already known about this topic? The skin is the first organ that demonstrates changes in response to zinc deficiency. Zinc levels are tightly regulated by zinc‐transporting proteins: the ZIP family and the zinc transporter family. ZIP10 is a crucial zinc transporter in murine epidermal development by supplying zinc to p63. Epigenetic changes by histone deacetylases and histone acetyltransferases (HATs) profoundly influence epidermal morphogenesis. The molecular mechanism underlying how zinc is involved in epigenetic regulation of skin homeostasis is largely unknown. What does this study add? ZIP10 is expressed in adult human skin, including skin appendages. ZIP10 regulates the activity of the zinc‐dependent epigenetic enzyme HAT, and ZIP10 depletion resulted in epidermal malformations in a reconstituted human skin model. What is the translational message? Based on bioinformatics analysis for gene sets regulated by ZIP10 knockdown and HAT inhibition, ZIP10 and HATs were closely linked with the regulation of genes related to epidermal homeostasis, particularly filaggrin and metallothionein. Linked Comment: Ogawa. Br J Dermatol 2019; 180 :707–709 . Respond to this article